Application of cysteinyl prolyl ester for the synthesis of cyclic peptides containing an RGD sequence and their biological activity measurement - Yamada, Akina; Takei, Toshiki; Kawakami, Toru; Taniguchi, Yukimasa; Sekiguchi, Kiyotoshi; Hojo, Hironobu (Frontiers in Chemistry, 2024)
Cysteinyl RGD-peptidyl cysteinyl prolyl esters, which have different configurations at the two cysteines and proline residues, were synthesized by the solid-phase method and cyclized by the native chemical ligation reaction. The cyclization efficiently proceeded regardless of the difference in the configuration to give cyclic peptides. The peptides were further derivatized to the corresponding desulfurized or methylated cyclic peptides at the Cys residues. The inhibition activity to the avb6 integrin binding was then analyzed by ELISA. The results showed that the activity is varied depending on the difference in the configuration and modification of the CPC moiety, demonstrating the usefulness of this method for the search of a good inhibitor of the protein-protein interaction.